2021
DOI: 10.3390/membranes11070531
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ar/O2 Plasma-Treated Polypropylene Membranes Applied for Membrane Distillation

Abstract: In the present work, Ar/O2 plasma treatment was used as a surface modification tool for polypropylene (PP) membranes. The effect of the plasma conditions on the properties of the modified PP surface has been investigated. For this purpose, the influence of gas composition and its flow rate, plasma power excitation as well as treatment time on the contact angle of PP membranes has been investigated. The properties of used membranes were determined after various periods of time: immediately after the modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Because of its greater complexity and the greater robustness of the resulting membranes, plasma treatment has received the least attention in the last five years [137]. Plasma does not require any pretreatments on the membrane surface and is strongly influenced by the exposure time.…”
Section: Propertymentioning
confidence: 99%
“…Because of its greater complexity and the greater robustness of the resulting membranes, plasma treatment has received the least attention in the last five years [137]. Plasma does not require any pretreatments on the membrane surface and is strongly influenced by the exposure time.…”
Section: Propertymentioning
confidence: 99%
“…In order to prevent these problems, it is important to use water treatment applications and to control the quality of natural, drinking, or artificial water sources and basins [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In water treatment systems, membranes are frequently used as a quality control medium combined with the filtering function. They are technical barriers of selectively permeable phases that allow water to pass through but prevent the passage of unwanted substances in water treatment [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. New approaches and research are being carried out on water treatment in an environmentally friendly way using less energy, fewer chemicals, and fewer artificial light sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Gryta et al [14], showed the use of Ar/O 2 plasma treatment in the surface modification of polypropylene (PP) membranes. This plasma treatment significantly changed the surface to a depth of less than 1 micron, with significant increases in porosity that facilitated mass transport-thus increasing flux within the membrane.…”
mentioning
confidence: 99%